Modulation of G-protein activation, calcium currents and opioid receptor phosphorylation by the pH-dependent antinociceptive agonist NFEPP - Celik, Melih Özgür; Seitz, Viola; Yergöz, Fatih; Dembla, Sandeep; Blum, Nina Kathleen; Schulz, Stefan; Stein, Christoph (Frontiers in Molecular Neuroscience, 2023)
N-(3-fluoro-1-phenethylpiperidine-4-yl)-N-phenyl propionamide is a newly-designed pain killer selectively activating G-protein-coupled mu-opioid receptors (MOR) in acidic injured tissues, and therefore devoid of central side effects which are typically elicited at normal pH values in healthy tissues. However, the neuronal mechanisms underlying NFEPP’s antinociceptive effects were not examined in detail so far. Voltage-dependent Ca2+ channels (VDCCs) in nociceptive neurons play a major role in the generation and inhibition of pain. In this study, we focused on the effects of NFEPP on calcium currents in rat dorsal root ganglion (DRG) neurons. The inhibitory role of the G-protein subunits Gi/o and Gβγ on VDCCs was investigated using the blockers pertussis toxin and gallein, respectively. GTPγS binding, calcium signals and MOR phosphorylation were also investigated. All experiments were performed at acidic and normal pH values using NFEPP in comparison to the conventional opioid agonist fentanyl. At low pH, NFEPP produced more efficient G-protein activation in transfected HEK293 cells and significantly reduced VDCCs in depolarized DRG neurons. The latter effect was mediated by Gβγ subunits, and NFEPP-mediated MOR phosphorylation was pH-dependent. Fentanyl’s responses were not affected by pH changes. Our data indicate that NFEPP-induced MOR signaling is more effective at low pH and that the inhibition of calcium channels in DRG neurons underlies NFEPP’s antinociceptive actions.